2017
DOI: 10.1186/s12199-017-0680-1
|View full text |Cite
|
Sign up to set email alerts
|

Rare variants of RNF213 and moyamoya/non-moyamoya intracranial artery stenosis/occlusion disease risk: a meta-analysis and systematic review

Abstract: BackgroundThe p.R4810K and other rare variants of ring finger protein 213 gene (RNF213) were illustrated as susceptibility variants for moyamoya (MMD) and non-moyamoya intracranial artery stenosis/occlusion disease (ICASO) recently. However, the effect sizes of p.R4810K were in great discrepancy even in studies of the same ethnic population and firm conclusions of other rare variants have been elusive given the small sample sizes and lack of replication. Thus, we performed this study to quantitatively evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
0
7

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 49 publications
3
46
0
7
Order By: Relevance
“…11 The RNF213 c.14429G>A (p.Arg4810Lys, rs112735431) variant is a founder mutation and found as the risk allele for Moyamoya disease in the East Asian population, with a high odds ratio. 11,12 Intriguingly, the penetrance of this specific founder mutation must be low, but if disease phenotypes based on this mutation appear, vascular diseases in several organs, at least in the brain and lung, are induced. 5,6 We previously reported one family with the RNF213 p.Arg4810Lys variant in which the mother developed PAH (Case #4), and her daughter exhibited Moyamoya disease, 3 suggesting the presence of RNF213-associated vascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…11 The RNF213 c.14429G>A (p.Arg4810Lys, rs112735431) variant is a founder mutation and found as the risk allele for Moyamoya disease in the East Asian population, with a high odds ratio. 11,12 Intriguingly, the penetrance of this specific founder mutation must be low, but if disease phenotypes based on this mutation appear, vascular diseases in several organs, at least in the brain and lung, are induced. 5,6 We previously reported one family with the RNF213 p.Arg4810Lys variant in which the mother developed PAH (Case #4), and her daughter exhibited Moyamoya disease, 3 suggesting the presence of RNF213-associated vascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond the association with MMD, a number of studies have reported frequent RNF213 variants in patients with non-MMD ICASO [2,31,32]. In a meta-analysis of 11 studies including 1778 ICASO patients and 3140 controls in East Asians, RNF213 4810G > A was significantly associated with an increased risk of ICASO [17]. High-resolution magnetic resonance angiography (MRA) showed that ICASO with RNF213 4810G > A was associated with a negative remodeling pattern, which is a hallmark of MMD, in contrast to the positive remodeling pattern of classical atherosclerotic ICASO [33].…”
Section: Discussionmentioning
confidence: 99%
“…The RNF213 gene encodes a RING finger protein that possesses both ubiquitin ligase activity and ATPases associated with diverse cellular activities' (AAA+) ATPase activity [16]. Although RNF213 variants have been associated with various vascular disorders, the mechanisms through which they contribute to these disorders are unknown [17]. Experimental reports have suggested multiple pathogenic mechanisms involving endothelial function, smooth muscle cell proliferation, inflammatory signaling pathways, hemostasis, angiogenesis, vascular remodeling, and response to hypoxia [7,9,10,[18][19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Constitutional hotspot variants in RNF213 have been reported in a variety of subsequent studies (Hitomi et al, ; Liu et al, ; Ma et al, ; Roder et al, ). The RNF213 mutation p.R4810K was confirmed to be associated with familial MMD risk in Japan, Korea, and China in a meta‐analysis and systematic review (Liao, Deng, Dai, Zhang, & Yan, ). Several patients with PHACE syndrome and MMV have been reported (Jack et al, ; Sathishkumar, George, Irodi, & Thomas, ; Schilter et al, ; Tortora et al, ).…”
Section: Evidence For a Genetic Basis And Clues For Timing During Devmentioning
confidence: 97%